Help-Seeking Intention in Obsessive-Compulsive Disorder: Predictors and Barriers in South Africa - Hathorn, Sarah Kate; Lochner, Christine; Stein, Dan J.; Bantjes, Jason (Frontiers in Psychiatry, 2021)
Introduction: Many individuals with obsessive-compulsive disorder (OCD) delay seeking help, leading to greater illness severity, additional comorbidity, and increased functional impairment. Patterns of help-seeking for OCD have however not yet been described in South Africa, a low- and middle-income country with many health service challenges. Study aims were to identify predictors of and barriers to help-seeking among South Africans with OCD. Methods: Fifty adults with OCD completed an online survey to assess 1) socio-demographic characteristics, 2) OCD symptom severity, 3) treatment barriers, 4) perceived treatment benefits, 5) self-efficacy, and 6) help-seeking intention. Multiple linear regression analysis was used to establish predictors of help-seeking intention. Descriptive statistics were used to determine the most endorsed help-seeking barriers. Results: 42.6% of the variance in help-seeking intention was explained by the investigated constructs (R^2 = 0.426, F = 4.45 p < 0.01). Perceived treatment benefits were the only significant predictor of help-seeking intention (B = 1.37, t = 5.16, p < 0.01). More than a third (36%) of the sample endorsed wanting to handle the problem independently as a significant barrier, followed by treatment concerns (26%), affordability (22%), and embarrassment/shame (20%). Conclusion: Predictors of and barriers to help-seeking intention have not been well-studied. An innovative analysis of help-seeking patterns suggested that perceived treatment benefits were the only significant predictor of help-seeking intention among South African adults with OCD. Psychoeducation and mental health literacy programmes may be useful in increasing public appreciation of the benefits of OCD treatment, and in mitigating key help-seeking barriers.